Superior wave-absorbing performances of silicone rubber composites via introducing covalently bonded SnO2@MWCNT absorbent with encapsulation structure. (December 2020) - Zhao, Jia; Zhang, Junliang; Wang, Lei; Li, Jiakun; Feng, Tao; Fan, Juncheng; Chen, Lixin; Gu, Junwei
Abstract: SnO2 @MWCNT wave absorbent was firstly fabricated via a hydrothermal process followed by heat treatment. Then SnO2 @MWCNT/silicone rubber wave-absorbing composites were obtained by solution casting method. XRD, Raman, TGA, XPS, and TEM analyses indicated the successful preparation of covalently bonded SnO2 @MWCNT absorbent with encapsulation structure. When the mass fraction of SnO2 @MWCNT was 7.5 wt% and the sample thickness was 2.6 mm, the SnO2 @MWCNT/silicone rubber wave-absorbing composite displayed the minimum reflection loss (RLmin ) of −56.9 dB and effective absorption bandwidth (EAB) of 3.1 GHz. The outstanding wave-absorbing performances of SnO2 @MWCNT/silicone rubber wave-absorbing composites could be ascribed to the excellent impedance matching and dielectric loss capability. Furthermore, the corresponding 7.5 wt% SnO2 @MWCNT/silicone rubber wave-absorbing composite exhibited heat resistance index ( T HRI ) of 196.3 °C, higher than that of neat silicone rubber (187.4 °C). Highlights: The covalently bonded SnO2 @MWCNT wave absorbent with encapsulation structure was successfully prepared. SnO2 @MWCNT/silicone rubber wave-absorbing composites demonstrated superior wave-absorbing performances and thermal stability. 7.5 wt% SnO2 @MWCNT/silicone rubber wave-absorbing composites (2.6 mm) displayed RLmin of −56.9 dB and EAB of 3.1 GHz. The 7.5 wt% SnO2 @MWCNT/silicone rubber composite exhibited THRI of 196.3 °C, higher than that of silicone rubber (187.4 °C).